KONTRAK PSIKOLOGIS DAN WORK ENGAGEMENT DALAM MENINGKATKAN KEPUASAN KERJA DI PT ADHIKARYA - Adolf Hardeba (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This study aims to test whether there is influence of psychological contract and work engagement to job satisfaction. The sample of this research is 53 employees of Head Office of PT Adhi Karya (Persero) Tbk. with non-probability sampling method and incidental sampling technique. Multiple regression analysis is used as a technique to analyze data and test hypotheses. The results from this study is that there is a positive and significant influence between the psychological contract on job satisfaction, the positive and significant influence between work engagement to job satisfaction and positive influence and significant correlation between psychological contract and work engagement simultaneously on job satisfaction.